Influence of Father Absence on Self-Esteem of Secondary School Students in Keiyo Sub-County, Kenya - Magangi , Agnes B. (African Journal of Education,Science and Technology (AJEST), 2018)
Secondary schools in Kenya are the aboard of thousands of adolescents, whose needs cannot be ignored or wished away without future dire consequences to both the students and the world at large. The absence of the father in homes is an increasing trend in Kenya, and the belief that the absence of fathers is lined with a variety of social pathologies is gaining national momentum. This study was designed to investigate the effects of father absence on self-esteem among secondary school students. The study was based on John Bowlby’s attachment theory (2009). Descriptive research design was used in the study and the study targeted two hundred respondents. Purposive sampling was used to select students from father absent families while random sampling was used to select the students from father present families. The subjects were required to respond to a self-esteem inventory as a measure of their self-esteem. Data was analyzed using descriptive statistics. The study revealed that students from father absent family have low self-esteem as compared to their counterparts from father present homes. Further, boys from father absent family had low self-esteem while those from father present homes had high self-esteem. Majority of the boys from father absent parent family scored less than 8 out of 25 in the self-esteem inventory, which was below average. A total of 13 boys from father present family scored above 20 out of 25 on the self-esteem inventory. None of the boys from father present family scored less than 15 on the inventory. This clearly indicates that there is a significant difference in self-esteem of father absent and father present boys. It was also established that girls from father absent family had low self-esteem as compared to their counterparts from father present family. Most of the girls from father absent family scored between 13 and 15 on the self-esteem inventory while their counterparts from father present family scored between 19 and 25 on the self-esteem inventory. Therefore, there was a difference between the self-esteem of father absent and father present girls. The study suggests that students should be helped by their teachers and parent (parents) to have a positive feeling of them. This will help teachers and school administrators to know how to help students from father absent families.